Hacía el Estado de Mago, Analogía entre un viaje espiritual y la versatilidad vocal (2023)
This work shows an artistic, auditory and visual proposal about the construction of a voice that, in singing, grants the vocal versatility with which one wants to give way to development of an artist from his Subject, as the versatility and artistic integrity are reflected, during an initiation journey on the Method of the 11 Steps of Magic, which has with it the compilation of teachings and esoteric knowledge of initiatory cultures of humanity, which continue the same pattern to transform reality: Warrior, Merchant, Priest and Magician.